Structural models for analysis of reinforced concrete frame buildings with masonry infills - ALVA,G. M. S. (2019)
Abstract The behavior of single-storey, single-bay reinforced concrete infilled frame with masonry panel subjected to static horizontal load was studied using two structural models: i) equivalent strut model (ESM) and ii) model with two-dimensional finite elements for state stress plane (MEF). In the first model, an equivalent diagonal strut replaces masonry. The axial stiffness of this element is defined by evaluation of the equivalent diagonal width. In the second model, the infilled frame is modeling by two-dimensional finite elements, requiring the simulation of the sliding and separation between the wall surfaces and the reinforced concrete frame. Although equivalent strut models are more attractive for design, the formulas found in the literature to determine equivalent strut width provide very different values. In addition, most of these formulas ignore some parameters that may be important, such as beam flexural stiffness. For this reason, several numerical analysis were be carried out. The models simulated usual geometric and mechanical characteristics observed in reinforced concrete buildings. The results of the two-dimensional finite element modeling (by software ANSYS) were used as reference for the evaluation of the results provided by the equivalent strut model. The comparison of results allowed the assessment of the analytical expressions for evaluation of the equivalent diagonal width. Based on this assessment, a new expression is proposed for buildings with similar characteristics as analyzed in this paper. The results of numerical simulations with MEF models also allowed for an evaluation of stresses and the probable cracking pattern in infill walls.